FAKTOR-FAKTOR PELAYANAN PRIMA YANG MEMPENGARUHI KEPUASAN SISWA PADA MENTARI CERDAS BANJARMASIN - Syafril, Syafril; Fahmi, Muhammad; Rosiana Fadilah, Neti (Ensiklopedia Sosial Review, 2022)
This study aims to determine the factors of excellent service that influence the satisfaction of tutoring students at Mentari Cerdas Banjarmasin. The population and sample in this study were tutoring students at Mentari Cerdas Banjarmasin. The sample in this study was 48 students by filling out research questionnaires. The sampling technique used in this research is random sampling. namely the sampling technique based on population members who happen to be met and are willing to be respondents. This research is a quantitative descriptive research, which is a research method based on the philosophy of positivism, which is used to examine a particular population or sample. Judging from the objectives, this research is included in the research of hypothesis testing. A hypothesis is a temporary answer to a research problem whose truth still needs to be tested Keywords: Excellent Service, Student Satisfaction, Tutoring, Influence, Sampling